2018
DOI: 10.1053/j.gastro.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Subfamily 1 Group D Member 1 Regulates Circadian Activity of NLRP3 Inflammasome to Reduce the Severity of Fulminant Hepatitis in Mice

Abstract: In studies of Nr1d1 mice and human macrophages with pharmacologic activation of NR1D1, we found NR1D1 to regulate the timing of NLRP3 expression and production of inflammatory cytokines by macrophages. Activation of NR1D1 reduced the severity of peritoneal inflammation and fulminant hepatitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 59 publications
11
177
0
5
Order By: Relevance
“…We recently demonstrated that the nuclear receptor REV-ERB␣ plays a role in regulation of the NLRP3 inflammasome (15). Bone marrow-derived macrophages (BMDMs) from Rev-erb␣-null mice display elevated Nlpr3 and Il1b gene expression due to the inability of REV-ERB to suppress the expression of these genes (15). Given that ROR␥ often functions in a reciprocal manner to REV-ERB, we performed a similar experiment in BMDMs from ROR␥-null mice.…”
Section: Ror␥ Is Required For Normal Nlrp3 Inflammasome Activity In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that the nuclear receptor REV-ERB␣ plays a role in regulation of the NLRP3 inflammasome (15). Bone marrow-derived macrophages (BMDMs) from Rev-erb␣-null mice display elevated Nlpr3 and Il1b gene expression due to the inability of REV-ERB to suppress the expression of these genes (15). Given that ROR␥ often functions in a reciprocal manner to REV-ERB, we performed a similar experiment in BMDMs from ROR␥-null mice.…”
Section: Ror␥ Is Required For Normal Nlrp3 Inflammasome Activity In Mmentioning
confidence: 99%
“…Based on our data indicating that ROR␥ is required for normal expression of Nlrp3 and Il1b as well as our recent study describing the direct regulation of these genes by REV-ERB, a nuclear receptor that typically recognizes similar or identical response elements as ROR (18), we sought to determine whether ROR␥ directly binds to response elements in the pro-ACCELERATED COMMUNICATION: ROR␥ regulates the NLRP3 inflammasome moters of the Nlrp3 and Il1b genes. Two functional REV-ERB response elements were identified in the promoter of the Il1b gene and four were identified in the promoter of the Nlrp3 gene (15), and we focused on determining whether these were also bound by ROR␥ using ChIP (Fig. 3A).…”
Section: Ror␥ Response Elements Are Located In the Promoters Of The Nmentioning
confidence: 99%
“…NR1D1 is linked to the immune system, as it has been shown to repress Tolllike receptor 4, Cx3cr1, and IL-6 expression in macrophages 15 . Therefore, activated NR1D1 alleviates the progression of pneumonia and fulminant hepatitis 19,20 . NR1D1 regulates the inflammatory response; however, whether NR1D1 mediates the pathogenesis of RA and related mechanisms remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observation that hypoxia triggers release of ATP into the extracellular space [24,25], we became interested in whether the ATP level in murine PB changes in a circadian rhythm-dependent manner. We employed the term "zeitgeber; ZT" (translated from the German as "time giver" or "synchronizer"), which was introduced by Jürgen Aschoff, one of the founders of the field of chronobiology, to annotate time points of measurement: ZT1 for 7:00 am, ZT5 for 11:00 am; ZT13 for 7:00 pm, and ZT21 for 3:00 am.…”
Section: Diurnal Changes In the Pb Level Of Extracellular Atp Occur Imentioning
confidence: 99%
“…Diurnal Changes in Expression of the Circadian Clock Gene NR1D1 As Well as the Aim2, Nlrp1a, and Nlrp1b Inflammasomes Nuclear receptor subfamily group D member 1 (NR1D1) protein has recently been described as reducing the circadian activity of the Nlrp3 inflammasome during fulminant hepatitis in mice [25]. Therefore, we selected this circadian clock gene and evaluated the circadian changes in expression of NR1D1 mRNA in peripheral blood granulocytes.…”
Section: Diurnal Changes In the Expression Of Genes From The Nlrp3 Inmentioning
confidence: 99%